Correlation Between Tic Disorders and Serum 25-Hydroxyvitamin D Levels in Chinese Children - Wang, Simei; Xu, Quanmei; Wang, Anqi; Yuan, Fang; Luo, Xiaona; Wang, Yilin; Guo, Miao; Zhang, Yuanfeng; Zhang, Wenjing; Ji, Xiaobing; Ren, Yun; Chen, Yucai (Frontiers in Pediatrics, 2022)
Objective To explore the correlation between serum 25-hydroxyvitamin D levels and tic disorders (TDs) in Chinese children. Methods We selected 2960 children with TD and 2665 healthy controls, aged 5–14 years, from the Department of Neurology of the Shanghai Children’s Hospital. Serum 25-hydroxyvitamin D levels and degrees of vitamin D deficiency were compared between patients with TD and healthy children. Results The mean serum 25-hydroxyvitamin D level in the TD group was significantly lower than that in the control group (P < 0.001). The proportion of patients with 25-hydroxyvitamin D deficiency in the TD group was significantly higher than that in the control group. However, there was no correlation between 25-hydroxyvitamin D deficiency and the severity of TD. In addition, for age-wise comparison, mean levels of 25-hydroxyvitamin D and its deficiency in the TD group were the most significant in children over 9 years of age. Conclusion There is a correlation between 25-hydroxyvitamin D deficiency and TD in Chinese children, but not between 25-hydroxyvitamin D deficiency and the severity of TD. There was a correlation between age and deficiency of 25-hydroxyvitamin D; this deficiency was most pronounced among those over the age of 9 years.